DAR-PCR: a new tool for efficient retrieval of unknown flanking genomic DNA - Tianyi Sun; Mengya Jia; Lingqin Wang; Zhaoqin Li; Zhiyu Lin; Cheng Wei; Jinfeng Pei; Haixing Li (figshare, 2022)
Abstract Various PCR-based genome-walking methods have been developed to acquire unknown flanking DNA sequences. However, the specificity and efficacy levels, and the operational processes, of the available methods are unsatisfactory. This work proposes a novel walking approach, termed differential annealing-mediated racket PCR (DAR-PCR). The key to DAR-PCR is the use of primer-mediated intra-strand annealing (ISA). An ISA primer consists of a 5’ root homologous to the known sequence and a heterologous 3’ bud. In the single low-stringency cycle, the ISA primer anneals to a site on an unknown region and extends towards the sequence-specific primer (SSP) 1 site, thereby forming a target single-stranded DNA bound by the SSP1 complement and the ISA primer. In the subsequent more stringent cycles, its complementary strand is accumulated, owing to the differential annealing between the moderate-stringency ISA primer and the high-stringency SSP1. The accumulation of this strand provides an opportunity for ISA mediated by the ISA primer root. A loop-back extension subsequent to ISA occurs, creating a racket-like DNA with the known region positioned at both ends of the unknown sequence. This DNA is exponentially amplified during the secondary PCR driven by an SSP pair inner to SSP1. DAR-PCR was validated as an efficient walking method by determining unknown flanking sequences in Lactobacillus brevis and Oryza sativa.
Keywords: Biophysics; Biochemistry; 29999 Physical Sciences not elsewhere classified; Microbiology; Genetics; Molecular Biology; 69999 Biological Sciences not elsewhere classified; 110309 Infectious Diseases; Plant Biology; 60506 Virology